Analisis Rasio Keuangan untuk Mengukur Kesehatan Keuangan PT Telekomunikasi Indonesia, Tbk 2020-2023 - Nansi, Maria Regina; Mahendra, Rendy Surya; Ardiansyah, Ricky; Hadi, Mareta (Universitas Pahlawan Tuanku Tambusai, 2024)
PT Telekomunikasi Indonesia Tbk's financial health from 2020 to 2023 will be examined in this study using a number of financial ratios. Liquidity, solvency, profitability, and activity are among the ratios examined. The company's annual financial records served as the study's primary source of data. The analysis's findings indicate that PT Telekomunikasi Indonesia Tbk's financial situation is generally steady. The liquidity and solvency ratios, which show the company's capacity to fulfill both short- and long-term commitments, have increased. Nonetheless, over the course of the study, there were variations in the profitability and activity ratios. Stakeholders can use this study's insightful analysis to assess the company's financial performance and improve their strategic choices.